2018
DOI: 10.22441/mix.2018.v8i2.013
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Kebijakan Dan Makroekonomi Terhadap Efektivitas Penerimaan Pajak Di Bursa Efek Indonesia

Abstract: Abstract. The purpose of this research is to analyse the impact of policy and macroeconomic change on tax revenue and its effectiveness in Consumer Goods Industry sector (CGI) and Infrastructure, Utilities and Transport (IUT) sector. The analysis employed simultaneous equation system model estimated with 2SLS and simulation with Seidel method. Data was collected from annual report of the companies which listed on Indonesia Stock Exchange. The results showed that the change of tax receipts and effective tax rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Tax receipts and effective tax rates (ETR) are influenced by government policies and macroeconomic variables. Previous research has found that there is a greater impact of inflation, making tax revenues and effective tax rates (ETR) increase which is also followed by increases in tax rates, gross domestic product, exchange rates, and Bank Indonesia interest rates (Harahap, Sinaga, Manurung, & Maulana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tax receipts and effective tax rates (ETR) are influenced by government policies and macroeconomic variables. Previous research has found that there is a greater impact of inflation, making tax revenues and effective tax rates (ETR) increase which is also followed by increases in tax rates, gross domestic product, exchange rates, and Bank Indonesia interest rates (Harahap, Sinaga, Manurung, & Maulana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian oleh Saputro dan Meirinaldi (2021) menyebutkan bahwa stabilitas keamanan berpengaruh terhadap stabilitas makroekonomi melalui peningkatan pertumbuhan industri mampu memberikan dampak peningkatan stabilitas makroekonomi. Sedangkan perubahan kebijakan dan kondisi makroekonomi berpengaruh terhadap penerimaan pajak sesuai penelitian Harahap et al (2018).…”
Section: Pendahuluanunclassified
“…Kebijakan Pajak Indonesia dalam masa Pandemi COVID-19, kebijakan diterbitkan yang diberlakukan untuk dapat menjaga tercapai perolehan dana dari pajak dan efektivitas pengumpulannya. Salah satu kebijakan pajak adalah penetapan tarif pajak, maka perlu untuk membuat kebijakan oleh pemerintah atas penetapan tarif pajak yang sesuai atau efektif yang berimbas positif terhadap nilai investasi (Harahap, Sinaga, Manurung, & Maulana, 2018). Harapannya untuk menahan dampak pandemi virus corona pada ekonomi Indonesia.…”
Section: Hasil Dan Pembahasanunclassified